A case of glial fibrillary acidotic protein (GFAP) meningoencephalitis with rheumatoid arthritis - Mehri Salari; Masoud Etemadifar; Reyhaneh Soleymani; Aditya Ashok Murgai; Ronak Rashedi (Clinical Case Reports, 2023)
Abstract Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is an inflammatory disease of the central nervous system (CNS), which affects various regions in the CNS, presenting by variable clinical manifestations. Meningoencephalitis is the most common clinical presentation and association with autoimmune disorders has been reported in about 20% of these patients. Diagnosis is confirmed by the presence of CSF or serum immunoglobulin‐G (IgG) against GFAP. The reported case is a 53‐year‐old woman with the history of long‐standing rheumatoid arthritis who first presented with acute‐onset dizziness and gait disturbance, periventricular linear and radial enhancement pattern on MRI, and normal CSF analysis, successfully treated with an increase in the dose of oral steroids. After a year she had a subacute‐onset, moderate to severe holocephalic headache, normal neurologic examination and CSF analysis, and bilateral diffuse, pachymeningeal, and leptomeningeal enhancement on MRI. According to her Brain MRI imaging with relapsing remitting course steroid responsive ataxia and aseptic meningitis, her serum was tested for GFAP IgG antibodies which was positive. The reported patient is the first in the literature reported pachymeningitis in GFAP astrocytopathy. This case highlights the co‐occurrence of rheumatoid arthritis with GFAP‐associated astrocytopathy, and expands on the previously reported cases with similar association. This might also suggest a common immune pathogenesis.